CLINICAL AND LABORATORY CHARACTERISTICS OF CHRONIC VIRAL HEPATITIS B IN PREGNANT WOMEN - Yakubova Nigina Sadriddinovna; Djuraeva Kamola Stanislavovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
SUMMERY: The problem of viral hepatitis in pregnant women is one of the most pressing in modern medicine, since hepatitis B (HBV) and C (HCV) viruses are the most common cause of chronic liver diseases in women of childbearing age. According to the latest expert estimates, at the beginning of 2012, on average, 180 million people worldwide were chronically infected with the hepatitis C virus, and 35% of them were women of childbearing age. The problem of viral hepatitis in pregnant women is common to obstetricians, infectious disease specialists, hepatologists, and therapists, and requires the development of a common strategy for managing pregnancy in such women.